The effect of intraoperative lidocaine versus esmolol infusion on postoperative analgesia in laparoscopic cholecystectomy: a randomized clinical trial - Joshan Lal Bajracharya (BMC Anesthesiology, 2019)
Abstract Background As a part of multimodal analgesia for laparoscopic cholecystectomy, both intraoperative lidocaine and esmolol facilitate postoperative analgesia. Our objective was to compare these two emerging strategies that challenge the use of intraoperative opioids. We aimed to assess if intraoperative esmolol infusion is not inferior to lidocaine infusion for opioid consumption after laparoscopic cholecystectomy. Methods In this prospective, randomized, double-blind, non-inferiority clinical trial, 90 female patients scheduled for elective laparoscopic cholecystectomy received either intravenous (IV) lidocaine bolus 1.5 mg/kg at induction followed by an infusion (1.5 mg/ kg/h) or IV bolus of esmolol 0.5 mg/kg at induction followed by an infusion (5–15 μg/kg/min) till the end of surgery. Remaining aspect of anesthesia followed a standard protocol apart from no intraoperative opioid supplementation. Postoperatively, patients received either morphine or tramadol IV to maintain visual analogue scale (VAS) scores ≤3. The primary outcome was opioid consumption (in morphine equivalents) during the first 24 postoperative hours. Pain and sedation scores, time to first perception of pain and void, and occurrence of nausea/vomiting were secondary outcomes measured up to 24 h postoperatively. Results Two patients in each group were excluded from the analysis. The postoperative median (IQR) morphine equivalent consumption in patients receiving esmolol was 1 (0–1.5) mg compared to 1.5 (1–2) mg in lidocaine group (p = 0.27). The median pain scores at various time points were similar between the two groups (p > 0.05). More patients receiving lidocaine were sedated in the post-anesthesia care unit (PACU) than those receiving esmolol (p < 0.05); however, no difference was detected later. Conclusion Infusion of esmolol is not inferior to lidocaine in terms of opioid requirement and pain severity in the first 24 h after surgery. Patients receiving lidocaine were more sedated during their stay in PACU than those receiving esmolol. Trial registration ClinicalTrials.gov- NCT02327923. Date of registration: December 31, 2014.